IL‐33 induces production of autoantibody against autologous respiratory epithelial cells: a potential mechanism for the pathogenesis of COPD. Issue 2 (27th March 2019) - Li, Qin; Hu, Yue; Chen, Yan; Lv, Zhe; Wang, Jingjing; An, Gao; Du, Xiaonan; Wang, Huating; Corrigan, Chris J.; Wang, Wei; Ying, Sun
Summary: The mechanisms underlying the chronic, progressive airways inflammation, remodelling and alveolar structural damage characteristic of human chronic obstructive pulmonary disease (COPD) remain unclear. In the present study, we address the hypothesis that these changes are at least in part mediated by respiratory epithelial alarmin (IL‐33)‐induced production of autoantibodies against airways epithelial cells. Mice immunized with homologous, syngeneic lung tissue lysate along with IL‐33 administered directly to the respiratory tract or systemically produced IgG autoantibodies binding predominantly to their own alveolar type II epithelial cells, along with increased percentages of Tfh cells and B2 B‐cells in their local, mediastinal lymph nodes. Consistent with its specificity for respiratory epithelial cells, this autoimmune inflammation was confined principally to the lung and not other organs such as the liver and kidney. Furthermore, the serum autoantibodies produced by the mice bound not only to murine, but also to human alveolar type II epithelial cells, suggesting specificity for common, cross‐species determinants. Finally, concentrations of antibodies against both human and murine alveolar epithelial cells were significantly elevated in the serum of patients with COPD compared with those of control subjects. These data are consistent with the hypothesis that IL‐33 contributes to the chronic, progressive airways obstruction, inflammation and alveolar destruction characteristic of phenotypes of COPD/emphysema through induction of autoantibodies against lung tissue, and particularly alveolar type II epithelial cells. Abstract : In the present study, we address the hypothesis that airway inflammation characteristic of chronic obstructive pulmonary disease (COPD) is, at least in part, mediated by respiratory epithelial alarmin (IL‐33)‐induced production of autoantibodies against alveolar type II epithelial cells, which has specificity for common, cross‐species determinants. The presence of these autoantibodies identified from the serum of patients with COPD further confirms the potential role of autoimmune in pathogenesis of the disease.